PERAN MEDIA SOSIAL DALAM PROSES PENDIDIKAN INFORMAL GENERASI Z - Chanda maulana irawan; Nining Purwaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has brought significant changes to various aspects of life, including education. Social media is no longer used solely as a means of communication and entertainment, but has also become an important medium in informal education, particularly for Generation Z. Generation Z is a cohort that has grown up in the digital era and demonstrates a high level of engagement with social media platforms. This study aims to examine the role of social media in the informal education process of Generation Z, particularly in terms of knowledge acquisition, skill development, attitudes, and character formation. This research employs a qualitative approach using a literature review method. Data were collected through an analysis of relevant sources, including books, national and international journal articles, and previous studies related to social media, informal education, and the characteristics of Generation Z. The findings indicate that social media functions as an alternative learning resource that is flexible and easily accessible, a medium for fostering creativity and digital literacy, and a channel for internalizing social values such as tolerance, empathy, and social awareness. However, the use of social media in informal education also presents several challenges, including the spread of misinformation, digital addiction, and the potential emergence of negative behaviors such as cyberbullying and reduced face-to-face social interaction. Therefore, the active involvement of families and communities is essential in providing guidance and strengthening digital literacy so that social media can be utilized wisely and effectively to support the informal education of Generation Z. Keywords: Social media , Informal education , Generation Z